Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus - Miko, Ladislav (Zootaxa, 2008)
Porobelba weigmanni n. sp. (Oribatida: Damaeidae) is described, based on individuals found in the Pieniny Mountains of North-East Slovakia. It differs from previously known species of the genus by having long, hypertrophied notogastral setae c 1 , and by the presence of one pair of prodorsal tubercles. A new diagnosis of the genus Porobelba is presented. Two species—the American species P. parki Jacot, 1937 and the poorly described European species P. robusta Mihelcic, 1955—are removed from the genus, based on absence of a porose area on the notogaster, presence of propodolateral apophyses and other characters. A determination key for the three remaining species is presented.